Hubungan Pengetahuan, Pendidikan Ibu Hamil dan Pekerjaan Suami terhadap Kejadian Sifilis pada Ibu Hamil di Wilayah Kerja Puskesmas Muara Tembesi - Ketrin Yesi Berliana; Sulastri Sulastri (Jurnal Akademika Baiturrahim Jambi, 2023)
Syphilis is a sexually transmitted infection caused by Treponema pallidum which can cause quite severe conditions such as brain infections and body defects which can be dangerous if it occurs in pregnant women.  This type of research is Observational Analytics  with a cross-sectional research design which aims to determine the relationship between knowledge, education of pregnant women and husband's occupation of the incidence of syphilis in the Working Area of the Muara Tembesi Health Center in 2022. This research was conducted in February-April 2022 The population in this study was  all pregnant women in the working area of the Muara Tembesi Health Center in 2021 totaled 338 people with a sample of 77 respondents.  The sampling technique used is Proportionate Stratified Random Sampling.  Data collection used a questionnaire with univariate and bivariate analysis with the statistical test used was chi-square.  The results showed that there was a significant relationship between knowledge (ρ=0.003‹0.05), education (ρ=0.001‹0.05), and work (ρ=0.002‹0.05) on the incidence of syphilis in pregnant women.  ‹0.05).  It was concluded that the higher the knowledge, attitudes of pregnant women, and husband's support became the most dominant factors influencing the class of pregnant women